2005
DOI: 10.1111/j.1467-3010.2005.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens and the menopause – do they really help?

Abstract: Studies have recently questioned the safety of hormone replacement therapy (HRT) during the menopause with regard to an increased risk of breast cancer and heart disease. Most notably the US Women's Health Initiative and British Million Women Study resulted in a considerable media furore which has prompted women, who may previously have been happy to take HRT, to explore alternative approaches to the menopause. It is widely accepted that diet and lifestyle play a large part in symptom relief and evidence is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…[2][3][4][5] In one study, knowledge regarding the menopause and its treatment was reported to be lower among women with lower income groups. 6 It is commonly believed that many adverse climacteric symptoms can be avoided if woman and her family are sufficiently informed about the menopause and its management.7 Both women in midlife and health professionals believe that attitudes play a role in the experience of menopause, 8 with results from three longitudinal studies supporting this belief.9-11 However, the majority of studies have been conducted among Western, predominantly Caucasian, women. It is documented in several studies that the attitudes of Asian women are different from the western women towards the menopause as Asian women feel themselves psychologically uplifted and more respectful in the society after attaining the menopause.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] In one study, knowledge regarding the menopause and its treatment was reported to be lower among women with lower income groups. 6 It is commonly believed that many adverse climacteric symptoms can be avoided if woman and her family are sufficiently informed about the menopause and its management.7 Both women in midlife and health professionals believe that attitudes play a role in the experience of menopause, 8 with results from three longitudinal studies supporting this belief.9-11 However, the majority of studies have been conducted among Western, predominantly Caucasian, women. It is documented in several studies that the attitudes of Asian women are different from the western women towards the menopause as Asian women feel themselves psychologically uplifted and more respectful in the society after attaining the menopause.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] In one study, knowledge regarding the menopause and its treatment was reported to be lower among women with lower income groups. 6 It is commonly believed that many adverse climacteric symptoms can be avoided if woman and her family are sufficiently informed about the menopause and its management. 7 Both women in midlife and health professionals believe that attitudes play a role in the experience of menopause, 8 with results from three longitudinal studies supporting this belief.…”
Section: Introductionmentioning
confidence: 99%
“…Soymilk, a by‐product from soybean manufacture, is increasingly included in western diets. This is in part because the isoflavones in soymilk can bring many benefits to peri‐ and postmenopausal women, including relief from hot flushes (Jefferson 2005), improved lipid profiles, protection against oxidative damage to DNA (Ryan‐Borchers and others 2006), and maintenance of bone health (Setchell and Lydeking‐Olsen 2003; Atkinson and others 2004; Lydeking‐Olsen and others 2004). …”
Section: Introductionmentioning
confidence: 99%
“…However, further studies to validate the efficacy of constituents from these species in hormone replacement therapy are necessary. 9 We previously reported on the isolation of isoflavones from Dipteryx odorata 10,11 and also on the isolation of ergostan-secosteroids (physalins) from P. angulata. 12 In this work, phytochemical procedures using LC-MS 2 and GC-MS techniques to analyze an acetate fraction from C. esculenta crude methanol tuber extract, allowed the detection of glycosylated flavonoids and steroids capable of acting as estrogen-like compounds.…”
Section: Impact Statementmentioning
confidence: 99%